Social economic stratification in sports participation - Subhakti Prawira Raharja, Didik; Fauzi, Riza Sukma; Suryadin, Tatang; Rudi, Rudi; Yudha, Brio Alfatihah Rama; Nurhayati, Maya; Apriliani, Elsa Nur (Indonesian Journal of Sport Management, 2024)
Sports participation is influenced by a variety of factors that also influence it, sport is also one of the social activities carried out in society. The debate about socioeconomic status is the goal in looking at participation in sports. The survey was conducted in the sports community in Majalengka district with questions related to gender, age, place of activity, level of education, and income. The results show that the male sex with the late adolescent age range is more dominant in participating and the low level of education has a low percentage but the income level does not show a significant difference in doing physical activity.